Does Level of Received Intervention Dose Have an Impact on the Effectiveness of the Social Norms Alcohol Prevention Program The GOOD Life? - Vallentin-Holbech, Lotte; Rasmussen, Birthe Marie; Stock, Christiane (Frontiers in Public Health, 2019)
Background: Few studies have assessed how social norms messages are perceived and understood by adolescents in secondary school. We examined whether the self-reported level of exposure, satisfaction and recall of a social norms intervention had an impact on the preventive effect of the intervention The GOOD Life. Furthermore, we explored which factors were associated with high recall of the intervention. Methods: Data from pupils aged 13-17 years enrolled in a cluster-randomised controlled trial with 18 intervention schools (n=641) and 20 control schools (n=714) were analysed using multilevel regressions. The intervention provided social norms messages through three different communication elements: classroom feedback session, posters and web-application. At 3-months follow-up, pupils from the intervention schools were asked about their participation in, their satisfaction with and recall of the intervention. The effects were examined on: overestimation of peer drinking, binge drinking (5 or more drinks on one occasion) and alcohol-related harms. Results: Regards the outcome overestimation of peer drinking higher preventive effect sizes were observed for higher levels of exposure, satisfaction and recall. Regards the outcome alcohol-related harms preventive intervention effects were observed for medium exposure and higher satisfaction. For binge drinking we found no significant effects for any level of exposure, satisfaction or recall. Higher levels of satisfaction and exposure, and female sex were associated with better recall of the intervention. Conclusion: For higher levels of self-reported exposure, satisfaction and retention regarding the social norms messages we observed stronger intervention effects regards several outcomes suggesting that these implementation parameters are important for intervention effectiveness.